Retention of polysomy at 9p23-24 during karyotypic evolution in human breast cancer cell line COLO 824 - Savelyeva, Larissa; Claas, Andreas; An, Hanxiang; Weber, Ruthild; Lichter, Peter; Schwab, Manfred (Genes, chromosomes & cancer, 1999)
Somatic genetic alterations of 9p have been seen in a wide range of human cancers, including breast cancer. Loss of heterozygosity analysis of primary breast cancer tumors has revealed a high frequency of deletion of DNA from 9p21-22 encompassing the MTS1 (P16/CDKN2A) gene. We report the approximately tenfold increase in copy number of DNA from 9p23-24, which is far distal to P16/CDKN2A in female breast cancer cell line COLO 824, as revealed by fluorescence in situ hybridization, comparative genomic hybridization, and microsatellite analysis. Amplification of DNA has been reported previously to encompass multiple sites of the genome of the breast cancer cell, but increase in DNA copy number has not been seen in distal 9p. Genes Chromosomes Cancer 24:87-93, 1999. © 1999 Wiley-Liss, Inc.
Gesehen am 11.02.2019